Globalization and Language Evolution: The Impact of English on Contemporary Monacan and Indonesian Societies - Alyacitra Eka Dewi; Dedi Hermawan; Aprillia Priseyla Longdong (Proceeding of the International Conference on Language, Literature, and Culture Studies, 2024)
This paper examines the influence of globalization, particularly the spread of English, on the linguistic landscapes of Monaco and Indonesia. The study investigates how the introduction of English as a global lingua franca has affected local languages, cultural expressions, and communication practices in both countries. Using sociolinguistic frameworks, the paper discusses the positive and negative consequences of this linguistic evolution on national identity and cultural integrity.